Low-Fat Love: Expanded Anniversary Edition - Leavy, Patricia (Springer, 2016)
Low-Fat Love unfolds over three seasons as Prilly Greene and Janice Goldwyn, adversarial editors at a New York press, experience personal change relating to the men, and absence of women, in their lives. Ultimately, each woman is pushed to confront her own image of herself, exploring her insecurities, the stagnation in her life, and her reasons for having settled for low-fat love. Along with Prilly and Janice, the cast of characters’ stories are interwoven throughout the book. Low-Fat Love is underscored with a commentary about female identity-building and self-acceptance and how, too often, women become trapped in limited visions of themselves. Women’s media is used as a signpost throughout the book in order to make visible the context in which women come to think of themselves as well as the men and women in their lives. In this respect, Low-Fat Love offers a critical commentary about popular culture and the social construction of femininity. Grounded in a decade of interview research with young women and written in a fun, chick-lit voice, the novel can be read for pleasure or used as supplemental reading in a variety of courses in women’s/gender studies, sociology, psychology, popular culture, media studies, communication, qualitative research, and arts-based research. “Sometimes, when I read an especially wonderful book I say to myself, “I wish I had written that!” And that is how I feel about Low-Fat Love. To write a page-turner of a book that teaches about contemporary gender relationships is a major feat. Patricia Leavy has done that with Low-Fat Love. Brilliant!” Laurel Richardson, Ph.D., The Ohio State University “Patricia Leavy writes with passion, verve and skill. I will use this in my relational communication and women’s studies classes because it is beautiful, relatable, and offers smart critique of how pop-culture’s expectations for intimate relationships often lets us down. Leavy offers readers a way to think through their close relationships and demand better of themselves and others.” Sandra L. Faulkner, Ph.D., Bowling Green State University “I couldn’t put it down! Low-Fat Love is a remarkable novel that every women’s studies class and interpersonal class would do well to read. The title is indicative of the search for meaningful, deep, enriching relationships beyond the artificial, low-fat love that is all too pervasive in society today. I wholeheartedly recommend this book.” Robin Patric Clair, Ph.D., Purdue University “Low-Fat Love is absolutely brilliant. This new edition is a must-read for anyone who has lived, loved, dreamed, and at times, settled for less than what we deserve – in other words, this is a book for everyone.” Anne Harris, Ph.D., Monash University and Australian Research Fellow in Creativity and Arts in Education Patricia Leavy, Ph.D., is an internationally known independent scholar and novelist. She has published eighteen books including Method Meets Art: Arts-Based Research Practice and Fiction as a Research Practice. She was named the 2010 New England Sociologist of the Year by the New England Sociological Association and received the prestigious 2014 Special Achievement Award from the American Creativity Association. www.patricialeavy.com